Estrutura das assembleias de peixes de um riacho urbano e um rural no município de Londrina (PR) - Figueiredo, Victor Hugo de Almeida (2019)
Urbanization is a socio-economic process that may impact water bodies severely, especially springs, creeks and streams that tend to suffer more due to their smaller dimensions. Changes in the environment may disrupt fish assemblages, disturb physical and chemical water parameters and provoke other negative impacts. The aim of this study was to compare two streams within Londrina, Prananá (PR) using fish assemblage structure and composition data and limnological parameters; one of the streams is essentially urban (Cambé stream) and the other is a rural stream (Taquara stream). The collections were performed from 2013 to 2017 and were made at three points along the steams’ longitudinal gradient. The fishing methods included manual fishing (hand-held net, fishing net and sieves) and electric fishing (portable generator, transformer and hand-held net), each method had 40-minute sampling effort at each location. At Cambé stream, 3648 individuals and 23 species were collected, while at Taquara stream, 3170 individuals and 38 species were collected. In 2016, it was observed that high rainfall may have caused changes in the fish assemblages structure. The result found at Taquara stream demonstrates a consistency, confirming the hypothesis that this stream would have more defined fish assemblages structure and less dispersed results. Cambé stream, on the other hand, had dispersive results for its fish assemblages, and this result may be related with urbanization. The limnological data measured at both streams mostly comply with the limits allowed by ‘CETESB’(2009) and ‘Conama Resolution 357’. Data outside these limits were related to urbanization or weather events.